Efektivitas Terapi Relaksasi Benson dalam Mengurangi Gangguan Rasa Nyaman Nyeri pada Pasien dengan Post Operasi Laparoscopic Cholecystectomy - Neneng Indriyati; Ahmad Syaripudin; Lily Wahyuni (STIKES Columbia Asia Medan, 2026)
Patients who have undergone cholecystectomy generally experience acute pain due to the surgical incision, which, if not properly managed, can reduce comfort, hinder mobility, slow healing, and lower quality of life. One nonpharmacological therapy that can be administered is Benson relaxation therapy. This study investigates medical-surgical nursing care for patients undergoing post-operative laparoscopic cholecystectomy with the nursing issue of discomfort and pain. It employs a case study research design in the form of family-centered nursing care, involving 1 research subject with a medical diagnosis of cholelithiasis. Data collection instruments included an observation sheet and the Numerical Rating Scale (NRS). Results: Administration of Benson relaxation therapy once daily for 3 days, each session lasting 10 minutes, led to a reduction in pain scores when evaluated on the third day. Specifically, the first patient’s pain score was 6 before the intervention and decreased to 2 after the intervention. Conclusion: Benson relaxation therapy can reduce acute pain in patients following cholecystectomy. The results of this study can serve as a routine therapy for patients to perform when experiencing pain.